When are private standards more stringent than public standards? - Thijs Vandemoortele (Katholieke Universiteit Leuven, LICOS Centre for Institutions and Economic Performance, 2011)
Retailers' private standards are increasingly important in addressing consumer concerns about safety, quality and social and environmental issues. Empirical evidence shows that these private standards are frequently more stringent than their public counterparts. I develop a political economy model that may contribute to explaining this stylized fact. I show that if producers exercise their political power to persuade the government to impose a lower public standard, retailers may apply their market power to install a private standard at a higher level than the public one, depending on several factors.
Keywords: D72; L15; 330; private standards; public standards; political economy; Einzelhandel; Warenkennzeichnung; Standard; Marktmacht